The Interactions Pattern Teacher and Student in Online Learning Study of Fiqih Curriculum - Hidayatur Rohmah; Rika Anggraini (SCHOOLAR: Social and Literature Study in Education, 2021)
During the Covid-19 pandemic, almost all Indonesian institution of education adopted online learning. Departing from this phenomenon would appear the assumption that for the learning process to work properly it would need to be created an interaction pattern between good teachers and students. In this study, authors formulate how the patterns teacher and student interactions in online learning study of fiqih curriculum class VIII in MTsN 3 Jombang?. And what are some support factors and inhibitors teacher and student interactions in online learning study of fiqih curriculum class VIII in MTsN 3 Jombang?. Using a qualitative descriptive approach, researchers acted directely involved in the study. This study suggest that: The importance of teacher and student interactions in the learning process makes a teacher reuire an active role in the use of time, in the learning process the teacher brings forth his interactions and student to the purpose of learning, the teacher’s interaction and student must be present and properly awakened so that in the learning process goes well, when any student who deviates the teacher should be able to understand how to awaken the student, the teacher and student interaction pattern in online learning study of fiqih curriculum class VIII in MTsN 3 Jombang is the teacher-centered interaction pattern, there are support factors and inhibitor teacher and student interactions in online learning study of fiqih curriculum class VIII in MTsN 3 Jombang is factors that support an inadequate internet network and a good learning medium and a host of inadequate internet connections.